Did anomalous atmospheric circulation favor the spread of COVID-19 in Europe? - Sanchez-Lorenzo, A.; Vaquero-Martinez, J.; Calbó, J.; Wild, M.; Santurtun, A.; Lopez-Bustins, J. A.; Vaquero, J. M.; Folini, D.; Antón, M. (Environmental Research, 2021)
ISSN:0013-9351 ISSN:1096-0953